Pengaruh Meta Ads Terhadap Purchase Intention Produk Sgrow Melalui Customer Engagement Dan Brand Awareness - Haikal Vicky; Anjar Astono (STREAMING, 2026)
This study aims to analyze the effect of Meta Ads on the Purchase Intention of Sgrow products through the mediating roles of Customer Engagement and Brand Awareness. In today’s competitive digital marketing environment, businesses need effective social media advertising strategies to attract consumers and stimulate purchasing behavior. Meta Ads provide opportunities for companies to increase consumer interaction and strengthen brand recognition. This research employed a quantitative approach by surveying 120 social media users who had been exposed to Sgrow advertisements. The data were analyzed using Path Analysis with SPSS version 27 to examine the relationships among the variables. The results show that Meta Ads have a significant positive effect on both Customer Engagement and Brand Awareness. In addition, Customer Engagement and Brand Awareness significantly influence consumers’ Purchase Intention toward Sgrow products. The findings also indicate that both variables serve as mediators in the relationship between Meta Ads and Purchase Intention. These results suggest that effective Meta Ads strategies can enhance consumer engagement, increase Brand Awareness, and ultimately encourage stronger Purchase Intention.